Characterization of the total family risk among families with functional elder adults, in the area of "patio bonito", in bogotá, 2005 (2010)
This article is generated based on the results of a master's degree research that unveiled the characteristics of the total family risk among families with functional elder adults who are beneficiaries of the Care Program for the wellbeing of the elderly who are poor, of the Local Health Center, the "Centro Operativo Local de Kennedy", i.e. residents in the area of "Patio Bonito". Data was obtained using the RFT 7-70 instrument, designed by Dr. Pilar Amaya. The research showed in general terms the characteristics of family structures and the tabulation of total family risks having as high some 34,7%, as medium some 34,7% among the group of families; also it enable one to identify the sub categories and risk factor that are most frequent in such family systems, which may be useful as a tool when planning and carrying out health programs for families according to risk.